Analysis of three differential gpr systems for subsurface imaging - Varianytsia-Roshchupkina, L.A.; Gennarelli, G.; Soldovieri, F.; Pochanin, G.P. (Радіофізика та електроніка, 2014)
The goal of this work is to analyze and compare possibilities of imaging using differential antenna systems with receiving antennas displaced symmetrically with respect to the transmitting antenna along three orthogonal directions. To this end, synthetic radargrams are generated by the finite-difference time-domain forward solver for each measurement setup. After that a microwave tomographic approach is applied to process the scattered field differential data and to facilitate the comparison among these systems. As a result, it was obtained that the system with antennas displaced along the vertical axis is the only one capable to provide a reliable image regardless of the shape of the object. The performed studies have shown the prospects of such system application in the practical GPR problems. Цель работы состоит в том, чтобы проанализировать и сравнить визуализационные возможности дифференциальных конфигураций антенных систем, составленных из приемной антенны – передающей антенны – приемной антенны, в которых приемные антенны симмет-рично смещены относительно передающей антенны вдоль трех ортогональных направлений. Для этого выполнено FDTD-моделирование радарограмм для каждой измерительной конфигурации. Для обработки дифференциальных данных полей рассеяния и сравнения между системами использован метод микроволновой томографии. Установлено, что только система с вертикально разнесенными антеннами способна обеспечить наиболее реалистичное изображение независимо от формы исследуемого объекта. Проведенные исследования показали перспективность применения такой системы в практических задачах георадиолокационного зондирования. Мета роботи полягає у тому, щоб проаналізувати й порівняти візуалізаційні можливості диференційних конфігурацій антенних систем, що складаються з приймальної антени – передавальної антени – приймальної антени, у яких приймальні антени симетрично зміщені відносно передавальної антени вздовж трьох ортогональних напрямків. Для цього виконано FDTD-моделювання радарограмм для кожної вимірювальної конфігурації. Для обробки диференційних даних полів розсіювання та порівняння між системами використано метод мікрохвильової томографії. Встановлено, що тільки система з вертикально рознесеними антенами здатна забезпечити найбільш реалістичне зображення незалежно від форми досліджуваного об’єкта. Проведені дослідження показали перспективність застосування такої системи в практичних задачах георадіолокаційного зондування.